The deactivation pathway of one-dimensional zeolites, LTL and ZSM-12, for alkylation of isobutane with 2-butene - Yoo, K; Smirniotis, PG (ELSEVIER, 2003)
This study focused on the deactivation pathway of one-dimensional zeolites, namely LTL and ZSM-12, during alkylation of isobutane with 2-butene at 80 degreesC and 300 psig. LTL possesses a one-dimensional pore with aperture of 7.1 Angstrom connected with large void spaces of 12.6 A, while ZSM-12 possesses a one-dimensional non-interconnecting tubular-like channel structure (pore size 5.6 Angstrom x 6.1 Angstrom). In the entire feed conditions (isobutane/2-butene molar ratios of 300, 98 and 20), both zeolites displayed different deactivation pathways. The product distribution over LTL sample barely changed even though olefin conversion dropped from 100 to 60%. This is in contrast to the common observation that the product distribution changes with loss of catalytic activity. For the ZSM-12 sample, a variation in the product distribution was observed with catalyst deactivation. This result supported the fact that LTL deactivated mainly by pore blockage but ZSM-12 deactivated due to site coveraoe. This is believed to be a result of the specific pore architecture of both zeolites. The coking materials deposited inside the spent zeolites after under a relatively severe deactivating condition (isobutane/2-butene molar ratios of 20) were characterized by GUMS, TGA, and TPO. These results also support the proposed deactivation pathway for both zeolites. (C) 2003 Elsevier Science B.V. All rights reserved.
Keywords: CATALYSTS; ACIDITY